Perancangan ISO 9001:2015 Pada PT. Visi Mulia Indonesia - Fransiscus Ryan Halim; Felecia Felecia (Jurnal Titra, 2018)
This study is done to desigin ISO 9001:2015 at PT. Visi Mulia Indonesia. PT. Visi Mulia Indonesia produce non-carbon NCR paper. Currently they don’t have a well-documented management system to maintain their quality. This research is conducted to help PT. Visi Mulia Indonesia designing and implementing ISO 9001:2015 quality management system. ISO 9001:2015 design conducted to 11 department of PT. Visi Mulia Indonesia, the research method is field study, literature study, gap analysis, risk analysis, gap fulfillment, improvement implementation, verification, audit, final gap analysis, and conclusion. The first gap analysis shows that only 27.54% document required by ISO 9001:2015 is available, and only 11.12% implemented at PT. Visi Mulia Indonesia. There are 3 quality-manual, 36 SOP, and 84 documents created and revised. After implementation and management review, it is found that 100% document has been fulfilled and 85.36% has been applied.